Macauba (Acrocomia aculeata): promising source of nutrients and association with health benefits, a review (Research, Society and Development, 2023)
Macauba is widely distributed in Brazilian territory. In addition to being used in the biodiesel production and animal food, it is also rich in bioactive compounds. Therefore, the objective of this review is to present the nutritional composition, the main bioactive compounds, and the potential health benefits of macauba. Macauba has high content of carotenoids, tocopherols, proteins, phenolic compounds, oleic acid, and fiber. Due the presence of bioactive compounds, macauba have the potential to promote health and can be used to prevent or treatment chronic non-communicable disease. Furthermore, this fruit and their by-products can be used in the development of new food and pharmaceutical products, promoting benefit family farming and contribute to the health benefits.